New “Inspirations” in Philosophical Anthropology - Corvino, Pier Francesco (Poligrafi, 2023)
This paper aims to endow the contamination of ecological wisdom with human and political ecology by outlining the basic features of a renewed philosophical anthropology. With this purpose, the concept of human nature is investigated here, using an ecological, eco-critical and integral framework, known as “inspiratory.” The key concept of this framework is to be found in the seemingly antiquated notion of temperament, which will be archeologically recovered and philosophically enhanced.